Aspirin use correlates with survival in women with clear cell ovarian cancer - Wield, Alyssa M. (Gynecol Oncol Rep, 2018)
Data from colon, breast and prostate cancers suggest that aspirin users have reduced mortality. While the direct mechanism remains uncertain, aspirin can suppress the COX-dependent and independent pathways involved in tumor progression. We hypothesized that aspirin users with clear cell ovarian cancer would have improved survival outcomes. We performed a retrospective review of patients with clear cell ovarian cancer diagnosed between 1995 and 2010, and followed outcomes through 2016. Patients underwent primary cytoreductive surgery followed by platinum-based chemotherapy. Aspirin use was defined by medication documentation in two records more than six months apart. Statistical tests included Fisher's exact, Kaplan-Meier and Cox regression analyses. Seventy-seven patients met inclusion criteria. Fifty-four patients (70%) had stage I-II disease. Thirteen patients (17%) used aspirin. Aspirin users had a statistically longer disease-free survival compared to non-users (HR 0.13, p = .018). While median disease-free survival was not reached for either group, 1 of 13 (8%) aspirin users recurred at 24 months, compared to 18 of 64 (28%) non-users. Aspirin users demonstrated longer overall survival (HR 0.13, p = .015). Median survival was not reached for aspirin users, compared to 166 months for non-users. Aspirin use retained significance (HR 0.13, p = .044) after controlling for age, stage and cytoreductive status. In this small cohort of women with clear cell ovarian cancer, aspirin use correlated with improved disease-free and overall survival, and retained independent significance as a positive prognostic factor. Further research is warranted to confirm these findings before considering aspirin as a therapeutic intervention.